PENGEMBANGAN MEDIA PEMBELAJARAN BERUPA WAYANG KERTAS UNTUK PEMBELAJARAN BERBICARA BAHASA JERMAN TINGKAT DASAR - Ahmad Zulfikar Ali Akbar, - (2022)
The German Language is one of the second foreign language lessons that students learn in Senior high school and Madrasah Aliyah (MA). There are four necessary language skills in learning German, namely listening (Hören), speaking (Sprechen), reading (Lesen) and writing (Schreiben). Speaking (Sprechen) is one of the required skills that should be mastered by the students because with speaking skills students can convey their desires, ideas and opinions verbally. However, in practice students still face difficulties in speaking German. Therefore, paper wayang media is developed in order to overcome these difficulties. Paper wayang media is a learning media that was built from paper in the form of cartoons or real pictures with sticks to be moved. The research aims to build, implement paper wayang learning media in German speaking lessons as well as to know the opinions of the teacher and students about the usage of paper wayang media learning media in the class. The research method is Research and Development method. Researchers involved the teacher and students of XI-MIPA I SMA PGII 2 Bandung as respondents that give its evaluation of the developed product in the form of paper wayang. The development process of paper wayang media consisted of information gathering, planning, preliminary form development, product testing and product revision. The result of the research is eight wayang characters. The eight wayang characters consisted of two teenage boys, two men, two teenage girls and two women. Paper wayang have simple mechanisms to use and have swappable outfits, which can be adjusted to the necessary theme. The product assessment is carried out using the Likert scale through questionnaires distributed to the teacher and students. The teacher acts as a media and material expert giving an assessment of 97.77% (very good) on the paper wayang and gives an assessment of 97.50% (very Good) on the material used. The average assessment of paper wayang from the students is 96.42% (very good). Based on the results, it could be concluded that paper wayang is well received by the teachers and students as supporting media in learning to speak German in the class. These paper wayang media can still be better developed.